Strengths-based creative mindfulness-based group work with youth aging out of the child welfare system. Issue 4 (2nd October 2019) - Lougheed, Sean C.
ABSTRACT: This article describes the outcomes of a doctoral study exploring the facilitation of an arts and mindfulness-based group for youth aging out of the child welfare system. Although there has been an upsurge in attention to the use of mindfulness-based interventions (MBIs) with children, there are still significant knowledge gaps regarding the use of MBIs with older youth who have experienced trauma, loss, and marginalization. At the same time, there is increasing attention to the importance of relationships to successful transitions in the lives of youth aging out of child welfare system. This research is qualitative and sought to explore how an innovative MBI was experienced by these youth. Data from semistructured interviews revealed key themes related to the unique challenges of being involved in the child welfare system and the aging-out process, the participants' understanding and benefits of learning mindfulness, as well as their experience of social support through a collaborative group participation. The benefits of group participation, including meaningful engagement in the group process, are considered.